Hepatic Sarcoidosis: Natural History and Management Implications - Sedki, Mai; Fonseca, Nicholas; Santiago, Priscila; Diaz, Liege; Garcia-Buitrago, Monica; Mirsaeidi, Mehdi; Levy, Cynthia (Frontiers in Medicine, 2019)
Introduction: Hepatic granulomas are common in patients with sarcoidosis, but clinically significant liver disease is uncommon and poorly studied. We aimed to characterize the frequency and clinical course of hepatic sarcoidosis in an ethnically diverse population.Methods: This is a retrospective study including all cases of hepatic sarcoidosis in a single center. The median follow-up time was 49 months (4 – 121). Cases were identified based on ICD-9 and ICD-10 codes for granulomatous hepatitis, sarcoidosis, and hepatic sarcoidosis. Chi-square and Wilcoxon-signed rank test were used as indicated to assess for differences between groups. Results: Of 286 patients with sarcoidosis, 27 had hepatic involvement; 78% were female and 48% African-American. The most common pattern of liver tests abnormalities was cholestatic. Ten patients had clinically significant hepatic involvement: cirrhosis in seven (25.9%), portal hypertension in nine (33%), and portal vein thrombosis in one (3.7%). Gender, race, and ethnicity were not associated with an increased risk of hepatic involvement or symptomatic hepatic sarcoidosis. Most patients received medical treatment, most commonly oral glucocorticoids. At the end of the follow-up period, all patients were alive but two had undergone liver transplantation due to complications of hepatic sarcoidosis. Three patients with hepatic sarcoidosis had initially been classified as AMA-negative PBC. Conclusions: Hepatic sarcoidosis was found in 9.4% of patients with sarcoidosis and was clinically significant in 37% of those. Identifying and monitoring hepatic sarcoidosis is crucial given its potential complications.